In Vitro Pharmacokinetic/Pharmacodynamic Modeling of HIV Latency Reversal by Novel HDAC Inhibitors Using an Automated Platform. (June 2021) - Newhard, William; Patel, Munjal; Cassaday, Jason; Ballard, Jeanine; Squadroni, Brian; Wu, Guoxin; Liu, Jian; Yu, Wensheng; Kozlowski, Joe; Zuck, Paul; Howell, Bonnie; Hazuda, Daria; et al.
Antiretroviral therapy is able to effectively control but not eradicate HIV infection, which can persist, leading to the need for lifelong therapy. The existence of latently HIV-infected cells is a major barrier to the eradication of chronic HIV infection. Histone deacetylase inhibitors (HDACis), small molecules licensed for oncology indications, have shown the ability to produce HIV transcripts in vitro and in vivo. The pharmacologic parameters that drive optimal HIV latency reversal in vivo are unknown and could be influenced by such factors as the HDACi binding kinetics, concentration of compound, and duration of exposure. This study evaluates how these parameters affect HIV latency reversal for a series of novel HDACis that differ in their enzymatic on and off rates. Varying cellular exposure, using automated washout methods of HDACi in a Jurkat cell model of HIV latency, led to the investigation of the relationship between pharmacokinetic (PK) properties, target engagement (TE), and pharmacodynamic (PD) responses. Using an automated robotic platform enabled miniaturization of a suspension cell-based washout assay that required multiple manipulations over the 48 h duration of the assay. Quantification of histone acetylation (TE) revealed that HDACis showed early peaks and differences in the durability of response between different investigated HDACis. By expanding the sample times, the shift between TE and PD, as measured by green fluorescent protein, could be fully characterized. The comprehensive data set generated by automating the assays described here was used to establish a PK/PD model for HDACi-induced HIV latency reversal.